Legal framework of the nonprofit private sector in Peru - De Belaunde L. de R., Javier; Parodi Luna, Beatriz (Universidad del Pacífico, 1998)
The Political Constitution of Peru recognizes, as one of the basic human rights, the constitutional freedom of association in general. In Peru, the non-profit organizations are fundamentally regulated by the Civil Code, through the legal figures of association, foundation and committee, which are legal entities (incorporated organizations in Public Records). In addition, the Civil Code of Peru, recognizes non incorporated organizations (associations, foundations and committees) as legal subjects with a proper legal identity, though with a different regime of responsability.   In the non-profit sector of Peru, the most widely used figure is the association, because it allows the development of diverse activities whether of social interest or of mutual interest to its members, in different areas such as: culture, religion, sports, sindicates, international technical cooperation (NGO's), but they always must be non-profit. The foundation has not been as widely used in Peru as the case of the association. Nowadays, there is a debate in order to make important legal reforms of the foundations with the purpose of making them more dinamic. And, the committee has a rare application in Peru.   To conclude, it is important to mention that there are diverse non-profit organizations that act in the economic traffic, such as: NGO 's, communal organizations, educational institutions, sindicates. Most of these organizations do not have a proper legal identity as legal entities, so they have to use the classic figure of the association in order to have civil capacity.